Meat Sector Policy Note: Reducing Price Instability in the Mongolian Meat Market - Goodland, Andrew (World Bank, Washington, DC, 2013)
Meat plays an important role in the diets of the majority of Mongolians. Since the economic and political transition in the early 1990s, seasonal meat price fluctuations have become increasingly marked. In parallel, Mongolia is becoming increasingly urbanized, and urban consumers are dependent upon markets to access food, including meat, for household food security. These two trends have meant that a rising number of urban residents are vulnerable to fluctuations of price in one of their main staples. Government has responded to this by trying to influence the price of meat through a price stabilization policy under which public funds support the purchase and storage of meat and the release of these reserves during periods of peak prices. While some public intervention to smooth prices is a legitimate area for policy engagement, this policy note concludes that there is no evidence that the current policy has an impact on prices, and worse still, it may even discourage private meat storage. This is set in a context of relatively low budget allocation (by international standards) to the agricultural sector. What is required is a more comprehensive approach for developing the meat market and the livestock sector more broadly, and with regard to price stabilization, the consideration of a number of alternative policy responses that limits government expenditure and encourage market-based solutions.